Possible Sources of Data for Grade 8 Indicators - Ysseldyke, James E.; National Center on Educational Outcomes, Minneapolis, MN. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1995)
This booklet provides suggestions for possible sources of information for each of the student performance indicators listed in the National Center on Educational Outcomes' conceptual model for eighth-grade students, including students with disabilities. The model has eight outcome domains, each with several outcomes and indicators of outcomes. For each of the 73 indicators, several possible sources of information are listed. The eight outcome domains are: (1) presence and participation; (2) family involvement/accommodation and adaptation; (3) physical health; (4) responsibility and independence; (5) contribution and citizenship; (6) academic and functional literacy; (7) personal and social adjustment; and (8) satisfaction. Typical sources of information suggested are school or district statistics, attendance records, parent interviews, health screenings, teacher observations, test performance, student interviews, and student focus groups. (Contains 14 references.) (DB)
Availability: National Center on Education Outcomes, University of Minnesota, 350 Elliott Hall, 75 East River Road, Minneapolis, MN 55455 ($10).
Sponsoring Agency: Special Education Programs (ED/OSERS), Washington, DC.
Contract Number: H159C00004.
ERIC Note: For a related document, see ED 374 625.
Practitioners.
May also be available online. Address as at 14/8/18
Keywords: Disabilities; Educational Assessment; Evaluation Methods; Grade 8.; Information Sources; Junior High Schools; Measurement Techniques; Models; Outcomes of Education; Standards; Student Educational Objectives; Student Evaluation; Performance Indicators; Guides, Non-Classroom.